An exploratory study of creating opportunities out of solving societal challenges in the South African banking sector: A Creating Shared Value perspective - Moloi, Tsele (University of the Witwatersrand, Johannesburg, 2022)
The purpose of this study is to explore the Creating Shared Value (CSV) practices that the South African banking sector undertakes to create business opportunities out of solving societal challenges. Anchored on stakeholder theory, the study seeks to establish this potential link between the opportunity concept and societal challenges by deploying the qualitative multiple case study analysis of four major banks and the banking association of South Africa (BASA). The study proposes a CSV-opportunity conceptual framework. The research relied on a multi- method approach, including preliminary interviews, semi-structured in-depth interviews, document analysis, and field notes to collect qualitative data. Thematic content analysis and coding were deployed. The empirical findings suggest that CSV is mostly motivated and driven from a responsive business case (regulatory compliance, risk management, societal contract and legitimacy), a compelling societal case (desire for societal change), corporate societal initiatives (CSR, corporate philanthropy, corporate sponsorships) and a compelling business case (business opportunity). However, the compelling business case comes as a by-product or an after-thought of these other motivating factors. These motivating factors are leveraged as transitional vehicle and enabler of CSV business opportunities. This means that within social constructivism view, business opportunities are created regardless of the motivating driving factors. Findings further indicate that CSV is seen and understood as an extension of other related concepts. Most importantly, CSV is understood as an extension of the transformation of the banking sector and society to ensure that it is inclusive of many previously marginalised as a result of the country’s history of apartheid and its skewed economic activity. The empirical evidence shows that the stakeholder co-creation nature of CSV is both internal and external. Unlike CSV pioneers who presupposed CSV as a Utopian concept, free of trade- offs and challenges, the empirical results indicate a CSV that is fraught with both internal and external challenges. Internal challenges include measurement and trade-off challenges between business and society. The external challenges include external stakeholder co-creation and other external issues such as the deep-seated structural challenges of unemployment, poverty and inequality facing South Africa, all of which appear to hinder CSV interventions. Through the newly proposed CSV-opportunity framework, this study contributes to theory and practice. The study further demonstrates that CSV is indeed a social constructionist phenomenon where opportunity is subjectively constructed through actions and interactions with the social world
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Management to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Creating Shared Value; Opportunity; Societal value; Business value; UCTD; SDG-8: Decent work and economic growth